Developing a Novel Indolocarbazole as Histone Deacetylases Inhibitor against Leukemia Cell Lines - Wenjing Wang; Maomin Lv; Xiong Zhao; Jingang Zhang (Journal of Analytical Methods in Chemistry)
A novel indolocarbazole (named as ZW2-1) possessing HDAC inhibition activity was synthesized and evaluated against human leukemia cell lines HL-60 and NB4. ZW2-1 performed anti-population growth effect which was in a concentration-dependent manner (2–12 μM) by inducing both apoptosis and autophagy in cells. The compound also caused differentiation of HL-60 and NB4 cells as shown by increasing expression of CD11b, CD14, and CD38 at moderate concentration (4 μM). At relatively high concentration (8 μM), ZW2-1 significantly decreased intracellular histone deacetylase 1 level which was also observed. All the results indicated that ZW2-1 could be a novel antileukemia lead capable of simultaneously inducing apoptosis, autophagy, and differentiation.